Fabrication of a Nanosized g-C3N4-Loaded Cellulose Microfiber Bundle to Induce Highly Efficient Water Treatment via Photodegradation - Li, Anran (Langmuir : the ACS journal of surfaces and colloids, 2023)
Graphite carbon nitride (g-C3N4) with a suitable structure and strong amine activity is designed and prepared to serve as a hydrogen bond donor for the microfibrilization of corncob cellulose to form a cellulose microfiber (CMF) bundle. Simultaneously, well-dispersed nanosized g-C3N4 is loaded into the bundle to form a photocatalyst for efficient photodegradation of rhodamine B (Rh B) in water. Under the optimal preparation conditions at 165 °C, 10 min, and 0.08 mol/L H2SO4, the yield of g-C3N4-functionalized cellulose microfibers (CMF-g-C3N4) reaches to the highest over 70%. The catalytic rate of CMF-g-C3N4 is 3.3 times larger than that of pure g-C3N4. The degradation rate of Rh B is maintained at over 90% in 10 cycles of photocatalytic degradation. The obtained CMF-g-C3N4 also has good thermal stability and mechanical properties. This research suggests a particularly simple way to transform cellulose into a highly efficient photocatalyst for water treatment